2005
DOI: 10.1016/j.jmwh.2005.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery Curriculum for Auxiliary Maternity Nurses: A Case Study in the Dominican Republic

Abstract: Although most deliveries in the Dominican Republic occur within hospitals, maternal mortality in that nation remains high. In nonteaching hospitals, almost all of the vaginal births are attended by maternity auxiliary nurses. This article reports on a series of educational conferences for maternity auxiliary nurses in 1 hospital that were developed in response to the maternal mortality rate there. These conferences, taught by a team of midwives from the continental United States and Puerto Rico, used a midwife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The auxiliaries did not follow a routine, nurse‐driven, postpartum assessment that emphasized teaching and self‐monitoring. This study’s findings confirmed the research team’s preliminary observations (Foster et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…The auxiliaries did not follow a routine, nurse‐driven, postpartum assessment that emphasized teaching and self‐monitoring. This study’s findings confirmed the research team’s preliminary observations (Foster et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…This study was one of the outcomes of a continuing international partnership between US midwives (one trained in medical anthropology) and Dominican nurses that was initiated in 2003. Earlier activities of the partnership have been reported elsewhere (Foster, 2009; Foster & Heath, 2007; Foster et al, 2006; Foster et al, 2005). Following an increase in maternal mortality cases within a six month period, the Dominican nurses identified delays in accessing care for complications as a factor contributing to maternal deaths.…”
Section: Introductionmentioning
confidence: 85%
“…These steps also include knowledge development, such as calculation of gestational age and clinical history taking. Also attitude changes, such as more satisfaction with their jobs and feeling closer to the women under their care, are part of the documented changes as a result of the partnership (Foster, Regueira, Burgos, & Sanchez, 2005).…”
Section: Results Of the Partnershipmentioning
confidence: 99%
“…The proactive stance of the nurses to address the problem of maternal mortality helped to shape a highly participatory program. The successes, documented in initial outcomes in knowledge, attitudes, and skills among the all nurses (auxiliary and licensed), have been the building blocks for specific improvements in the quality of care (Foster et al, 2005). When the project began in 2003, there were 32 nurses assigned to the maternity ward, which includes a triage ward as well as labor, delivery, and postpartum, and most were auxiliary nurses.…”
Section: Results Of the Partnershipmentioning
confidence: 99%